Long-Term Quantitative Biodistribution and Side Effects of Human Mesenchymal Stem Cells (hMSCs) Engraftment in NOD/SCID Mice following Irradiation. (11th February 2014) - François, Sabine; Usunier, Benoit; Douay, Luc; Benderitter, Marc; Chapel, Alain
Abstract : There is little information on the fate of infused mesenchymal stem cells (MSCs) and long-term side effects after irradiation exposure. We addressed these questions using human MSCs (hMSCs) intravenously infused to nonobese diabetic/severe combined immunodeficient (NOD/SCID) mice submitted to total body irradiation (TBI) or local irradiation (abdominal or leg irradiation). The animals were sacrificed 3 to 120 days after irradiation and the quantitative and spatial distribution of hMSCs were studied by polymerase chain reaction (PCR). Following their infusion into nonirradiated animals, hMSCs homed to various tissues. Engraftment depended on the dose of irradiation and the area exposed. Total body irradiation induced an increased hMSC engraftment level compared to nonirradiated mice, while local irradiations increased hMSC engraftment locally in the area of irradiation. Long-term engraftment of systemically administered hMSCs in NOD/SCID mice increased significantly in response to tissue injuries produced by local or total body irradiation until 2 weeks then slowly decreased depending on organs and the configuration of irradiation. In all cases, no tissue abnormality or abnormal hMSCs proliferation was observed at 120 days after irradiation. This work supports the safe and efficient use of MSCs by injection as an alternative approach in the short- and long-term treatment of severe complications after radiotherapy for patients refractory to conventional treatments.